“Where Does My Hope Come From?”: P. D. James’s The Children of Men (1992) as a Christian Dystopia in the Context of the Late 20th Century Demographic Crisis - Suzanne Bray (Sillages Critiques)
While British dystopian works from the 1930s to the mid-1980s were primarily concerned with the fear of totalitarian regimes and/or nuclear war, by the last years of the twentieth century, the end of the Cold War meant that these worries were no longer so prevalent. One result was the appearance of several “demodystopias” or fictions concerned with the demographic crisis which was causing increasing concern in the developed world at the time. Although P. D. James’s The Children of Men (1992) has been compared with other demodystopias like The Handmaid’s Tale (1986) and Zoe Fairburns’ Benefits (1979) and described as a feminist work, it is far more of a Christian fable and contains echoes of Christian writers from Dostoevsky to T.S. Eliot. It also takes seriously the concerns of her contemporaries about declining birth-rates, an ageing population and an increasing dependency ratio. James joins in the discussion on these issues, but also asks what can give people hope and a reason to live in this ageing world. Her conclusion is that hope, and a meaningful life, are like happiness, things which are not found by specifically seeking for them, but are by-products of a life based on faith and love.